How mining companies promote gender equality through sustainable development? - Nattavud Pimpa (Taylor & Francis Group, 2019)
Gender equality has been promoted among social responsibility by mining companies. A key challenge for the management of sustainable development programs for gender equality is the need to develop sophisticated approaches that work at both local and international levels. In this paper, the researcher investigates the impact of CSR programs on gender equality (through labour, environment, training, and economic activities) and life experiences of female workers, members of the community, and their family in a mining community in the Southern Laos. The results show that CSR programs focusing on promoting equal opportunities at workplace, professional development, and other economic opportunities can influence the likelihood of sustainable development by mining companies.